Socio-demographic profile and compliance to Weekly Iron Folic Acid supplementation among adolescent girls in Central Delhi - Chauhan, Anuradha (Indian Journal of Community Health, 2015)
Background: Adolescence is a vulnerable period in the human life cycle for the development of nutritional anemia, particularly among girls. Objective: 1. To find out the prevalence of iron deficiency anemia in the study group. 2. To study the various socio-demographic factors associated with anemia. 3. To study the compliance of weekly Iron Folic acid Supplementation (WIFS). Material and Methods: A cross-sectional survey was conducted in an Urban Health Center, in New Delhi. A total of 60 adolescent females (10–19 years old) were included in this study. The study was undertaken from Nov 2013 – Dec 2013 (2 months) using a pre-tested questionnaire containing items to assess the socio-demographic profile, their medical history and past history. After taking their assent, hemoglobin (Hb) was estimated using HemoCue method. Results: The prevalence of anemia was found to be 71.1%. A significant association of presence of anemia was found with lower socio-economic status and non-intake of WIFS. Mean height and weight of subjects with anemia was significantly less in anemic girls than participants without anemia. Significant association of anemia was found with non-consumption of Iron Folic Acid (IFA) tablets (?2 value – 5.3, p value 0.02). Conclusions: A high prevalence of anemia among adolescent females was found, which was higher in the lower socio-economic strata and those not consuming WIFS. Thus there is a need to strengthen the programs for the prevention of anemia among adolescent girls through nutrition education and anemia prophylaxis.